TINY BRANCHED HAIR functions in multicellular trichome development through an ethylene pathway in Cucumis sativus L. (8th April 2021) - Zhang, Yaqi; Shen, Junjun; Bartholomew, Ezra S.; Dong, Mingming; Chen, Shuying; Yin, Shuai; Zhai, Xuling; Feng, Zhongxuan; Ren, Huazhong; Liu, Xingwang
Summary: The fruit trichomes of Cucurbitaceae are widely desired in many Asian countries and have been a key determinant of cucumber ( Cucumis sativus L.) cultivar selection for commercial production and breeding. However, our understanding of the initiation and development of cucumber trichomes is still limited. Here, we found that the cucumber TINY BRANCHED HAIR ( TBH ) gene is preferentially expressed in multicellular trichomes. Overexpression of CsTBH in tbh mutants restored the trichome phenotype and increased the percentage of female flowers, whereas silencing of CsTBH in wild‐type plants resulted in stunted trichomes with a lower rate of female flowers. Furthermore, we provide evidence that CsTBH can directly bind to the promoters of cucumber 1‐Aminocyclopropane‐1‐Carboxylate Synthase ( CsACS ) genes and regulate their expression, which affects multicellular trichome development, ethylene accumulation, and sex expression. Two cucumber acs mutants with different trichome morphology and sex morphs compared with their near‐isogenic line further support our findings. Collectively, our study provides new information on the molecular mechanism of CsTBH in regulating multicellular trichome development and sex expression through an ethylene pathway. Significance Statement: We explored the role of CsTBH in cucumber ( Cucumis sativus L.) trichome development by directly activating CsACS genes, providing new information on the molecular mechanism of CsTBH functioning in multicellular trichome development and sex expression through an ethylene pathway.